Inoculação com rizóbio em caupi no Sertão da Paraíba - SILVA, Ranieri Pereira da (2006)
A field experiment was conducted using a randomized block design, with four replicate, to evaluate rhizobial inoculation on cowpea [Vigna unguiculata (L.) Walp.] grown on a soil of the “Sertão da Paraíba” (Planossolo). Two native isolates from the soil, three RELARE recommended strains (BR 3267, INPA 3-11B e UFLA 3-84) and an UFRPE selected strain (NFB 700) were inoculated on cowpea cultivar CNCx 409- 11F. Two control treatments were also used: one with mineral nitrogen, and the other without added mineral nitrogen, both uninoculated. Nodulation (nodule number and dry mass), aerial part dry mass, N content and total N and relative efficiency, at 17 days after emergence were evaluated. It was observed significant effect to number and dry matter of nodules, dry matter, total N accumulated and relative efficiency of total N accumulated on shoot dry matter. The results suggest the occurrence of native rhizobial population in soil with effective nitrogen fixation on cowpea. Strains INPA 3-11B, BR 3267 and UFLA 3-84 were more effective on nodulation and nitrogen fixation than native rhizobia and strain NFB 700, when inoculated on cowpea grown in a Planossol of the “Sertão da Paraíba”. Nitrogen fertilization (50 kg ha-1) reducesnodulation and nitrogen fixation on cowpea.